Kaposi Sarcoma in Solid Organ Transplant Recipients: A challenging Case - Daniela Macedo; Pedro Miguel Garrido; Isabel Fernandes; Alice Santana; José Guerra; João Borges-Costa (Sociedade Portuguesa de Dermatologia e Venereologia, 2019)
Kaposi sarcoma is a low-grade vascular tumor, associated with human herpesvirus-8 infection. Solid organ transplant recipients have a much higher risk of this malignancy, with estimated incidence rates increased 84 to 500 times. The risk is even higher in some ethnic groups, already with a higher incidence of this disease.  We report a case of a 37-year-old African male, a kidney transplant recipient, with a Kaposi sarcoma refractory to different treatment options. The present case puts in evidence the challenges associated with the management of this disease in this high-risk population and highlights the role of a multidisciplinary approach to achieve effective treatment, particularly in advanced and refractory forms.